The Caliphate Materials of Fiqh Lesson at The Publisher of PT Karya Toha Putra Semarang - Nasrun Harahap; Imam Ghozali (Al Qalam, 2022)
This study examines the material for the caliphate in fiqh class XII at the publisher of PT Karya Toha Putra Semarang. In theory, the Khilafah material in this book is part of the discipline of siyasa fiqh which discusses the system of state and government. This book has given one side of the meaning of the caliphate in academic studies, the meaning of the caliphate varies among Islamic scientists. So that when it is presented as a class XII subject matter, there are various possibilities of having an exclusive view of the caliphate, so that when it becomes a subject of discussion among students it will mean that the Indonesian state is not a form of the caliphate and may carry out jihad, make changes or carry out resistance as in the next chapter in this book. talk about jihad. The purpose of this study is to examine some parts of the caliphate material that have the potential to develop negative perceptions of the Indonesian state system in Madrasah Aliyah students. In addition, this study also examines the perspective of the 2013 curriculum on the Khilafah material in the book written by Mundzier and Suparta. This type of research is a research library using a qualitative approach. The research steps are collecting research data related to the research material, outlining the material being studied, and analyzing and concluding the research. The results of the study indicate that the material for the caliphate in this book needs to improve the understanding of the caliphate which is more comprehensive than scientists, including Indonesian scientists. second, this material is still contrary to the philosophy of the 2013 curriculum which explains that education is rooted in the cultural values ​​of the Indonesian nation.